Code limitations on the procedural rights of the Military Gendarmerie against a soldier in active military service - Konarska-Wrzosek, Violetta; Ziółkowska, Agata (Studia Iuridica Toruniensia, 2021)
The article compares the procedural provisions (penal and minor) that define the procedural competence of the Military Gendarmerie (Military Police) against a soldier in active military service in a situation where he has committed a prohibited act. Comparative studies of the provisions of Article 312 of the Code of Criminal Procedure and Article 85 § 2 of the Code of Petty Ofences’ Procedure prompted the formulation of de lege ferenda proposals, indicating the need to amend the provision of Article 85 § 2 of the Code of Petty Ofences’ Procedure (and not only). Due to the matter subject to verification (with the use of linguistic and logical interpretation), which are selected provisions of the Code, this article uses research methods – comparative and qualitative (analytical).